Blacks in 1880s Toronto: The Search for Equality - McFarquhar, Colin (Ontario History)

(untitled) (The Ontario Historical Society, 2007)
By the 1880s Toronto had a well established black community. While Africans in Ontario’s largest city had achieved a certain amount of political equality, social and economic equality remained elusive. Using a number of examples this article attempts to show how blacks strived for full rights. Albert Jackson’s struggles to become a mailman, the attempts of the Fisk Jubilee Singers to be admitted to hotels, and the efforts to prevent Adam Morse from being extradited to the United States were issues that drew attention in Toronto in the 1880s. Blacks ultimately succeeded in these cases both because it was politically expedient and because leaders in the white community wanted the city to have a good reputation and avoid civic embarrassment.